DOI: 10.7190/shu-thesis-00025
|View full text |Cite
|
Sign up to set email alerts
|

Determining spatio-temporal metrics that distinguish play outcomes in field hockey

Abstract: Determining spatio-temporal metrics that distinguish play outcomes in field hockey Ciarán McInerney A thesis submitted in partial fulfilment of the requirements of Sheffield Hallam University for the degree of Doctor of Philosophy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 159 publications
(278 reference statements)
0
6
0
Order By: Relevance
“…This is emphasized by the findings of McInerney et al. 52 who reported that in attacking phases, “39% of circle entries occurred when the possessing player was within 15 m of the goal line with more opponents than teammates in his or her region, at the moment of the outcome” and that a smaller distance between the teams leftmost and rightmost player increased the chance of a circle entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is emphasized by the findings of McInerney et al. 52 who reported that in attacking phases, “39% of circle entries occurred when the possessing player was within 15 m of the goal line with more opponents than teammates in his or her region, at the moment of the outcome” and that a smaller distance between the teams leftmost and rightmost player increased the chance of a circle entry.…”
Section: Discussionmentioning
confidence: 99%
“…Physical output was relatively similar across match results for both ‘in possession’ and ‘not in possession’ instances. This may be due to the relatively short periods of possession within hockey (Table 3) and that other factors such as player spacing 52 and technical ability may play a larger role in match outcome. In contrast, a clear pattern exists in the Australian Football League – a physically demanding, contact based sport with similar relative physical output to hockey.…”
Section: Discussionmentioning
confidence: 99%
“…The backward dropping algorithm is a genomic selection method that reduces a large number of variables into a smaller subset that best distinguishes a trait. 30 This method was applied to the analysis of a small sample of games in hockey as it has the advantage of not needing a large number of observations (games) to build the model. 30 This can be an issue in hockey when there is limited international tournaments occurring and consequently limited information available per team.…”
Section: Performance Analysis Techniquesmentioning
confidence: 99%
“…30 This method was applied to the analysis of a small sample of games in hockey as it has the advantage of not needing a large number of observations (games) to build the model. 30 This can be an issue in hockey when there is limited international tournaments occurring and consequently limited information available per team. The aim was to identify relationships between spatio-temporal metrics and positive and negative outcomes of play.…”
Section: Performance Analysis Techniquesmentioning
confidence: 99%
See 1 more Smart Citation